Komparasi Mediamorfosis Pada Web Streaming Radio Idola Dan Radio Prambors Semarang - Melinda Fadyah Zahra; Heni Indrayani (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
The development of digital technology has changed media consumption patterns and encouraged traditional radio to adapt through web streaming services. This study compares the mediamorphosis of the web streaming platforms of Radio Idola FM and Radio Prambors FM Semarang as a strategy to face digital transformation. Using a descriptive qualitative approach with a case study method, data were collected through website observations and interviews with digital content managers. The findings show that Radio Idola FM emphasizes news, talk shows, and interview archives to maintain its adult audience. Meanwhile, Radio Prambors FM focuses on entertainment, music, podcasts, and interactive visual design to attract younger listeners. These findings indicate that mediamorphosis success is strongly influenced by audience segmentation and the integration of web streaming as an interactive medium.